New Tools, New Value: Producing Music after the Individual. Issue 2 (December 2015) - Robertson, Benjamin J.
Abstract : This essay explores the manner in which music production software, by granting to users the capacity to experience music in ways they cannot on their own, undermines the modern form of subjectivity known as individuality. It critiques Jacques Attali's prognostication of a network of musical composition, under which musicians produce for themselves according to their own codes and outside the codes established by established by a particular historical configuration of power; draws on examples of contemporary musical forms, namely the mashup; and discusses the manner in which Audacity and similar software allows users to 'see music'. Thus I demonstrate that the new tools of musical production instantiate what Jonathan Sterne calls 'perceptual technics', by which the human body becomes incorporated into the process of valorisation by virtue of an ability it lacks. Such incorporation draws our attention to the manner in which traditional Marxist understandings of the relationship of the human to the machine—assumptions which Attali shares—are no longer valid. Attali's postmodern understanding was a powerful means by which to critique modern forms of power and subjectivity, but under postmodern conditions, when the individual becomes a 'dividual', new critical tools and concepts are needed to address a valorisation irreducible to a labour understood as discreet from the tools it 'uses'.